Insolvency and debt overhang following the COVID-19 outbreak: Assessment of risks and policy responses - Demmou, Lilas (OECD Economics Department Working Papers, 2021)
This paper investigates the likelihood of corporate insolvency and the potential implications of debt overhang of non-financial corporations induced by economic shock associated with the outbreak of COVID-19. Based on simple accounting models, it evaluates the extent to which firms deplete their equity buffers and increase their leverage ratios in the course of the COVID-19 crisis. Next, relying on regression analysis and looking at the historical relationship between firms' leverage and investment, it examines the potential impact of higher debt levels on investment during the recovery. Against this background, the discussion outlines a number of policy options to flatten the curve of crisis-related insolvencies, which could potentially affect otherwise viable firms, and to lessen the risk of debt-overhang, which could slow down the speed of recovery